A CONCEPTUAL FRAMEWORK FOR MEASURING STAKEHOLDER PERCEPTION TOWARDS CORPORATE GOVERNANCE IN PRIVATE AND GOVERNMENT OWNED BANKS OPERATING IN INDIA - Venkatesh, Dr. Shanthi; Prasad, Mr. Arun; Raja, Dr. Archana (The journal of contemporary issues in business and government, 2021)
The extent, to which companies adhere to the fundamental principles of governance, is sure to boost the confidence of the investors and other stakeholders, as well as the business. Also, adequate and strong disclosure policies help companies to attract investments, and builds stakeholder loyalty This paper aims to give a conceptual framework for a potential research study on understanding the perceptions of stakeholders, vis-a-vis, the shareholders, investors, management, employees and the customers on the governance policies of the private and public sector banks operating in India. The study will attempt to throw light on the awareness and expectation levels of the different stakeholders considered and also aims at providing suggestions for improvement at the strategic and policy levels.